Consumer-Level Perceived Access to Health Services and Its Effects on Vulnerability and Health Outcomes. Issue 2 (April 2020) - Tanner, Emily C.; Vann, Richard J.; Kizilova, Elvira
Access to health services affects the well-being of millions of consumers. Although the topic of health-related access is regularly featured in popular and academic conversations, these conversations primarily concentrate on objective or situational access factors. This research focuses instead on consumers' subjective perception of access to better appreciate how personally experienced service availability and ease of access jointly determine consumers' access perceptions. The authors find that perceived access to health services (PAHS) offers insight into the relationships between access, perceived health vulnerability, and overall health. Through scale development and a series of three theory-testing studies, this work demonstrates the close link between PAHS and perceived vulnerability (Study 1), connects this relationship to overall health (Studies 1–3), and establishes behavioral changes associated with access-vulnerability concerns (Study 2). Moreover, Study 3 finds evidence for a "muting" effect of health system distrust on the relationship between PAHS and perceived vulnerability as well as an "amplifying" effect of health motivation on the relationship between perceived vulnerability and overall health. Together, these studies illustrate PAHS's relevance for explaining consumer vulnerability and overall health.